Recent Progress in TiO2-Mediated Solar Photocatalysis for Industrial Wastewater Treatment - Tong Zhang; Xiaoguang Wang; Xiwang Zhang (International Journal of Photoenergy)
The current paper reviews the application of TiO2-mediated solar photocatalysis for industrial wastewater treatment, starting with a brief introduction on the background of industrial wastewater and the development of wastewater treatment processes, especially advanced oxidation processes (AOPs). We, then, discuss the application of solar TiO2 photocatalysis in treating different kinds of industrial wastewater, such as paper mill wastewater, textile wastewater, and olive mill wastewater. In the end, we compare solar TiO2 photocatalysis with other AOPs in terms of effectiveness, energy, and chemical consumption. Personal perspectives are also given, which may provide new insights to the future development of TiO2 photocatalysis for industrial wastewater.